The Arbitration Act 1996 : a commentary - Harris, Bruce, 1945-; Planterose, Rowan; Tecks, Jonathan (Chichester, West Sussex, UK : Wiley Blackwell, 2014)
The most readable, useful, practical and user-friendly guide to the Arbitration Act 1996. The Arbitration Act 1996 is a section by section commentary on the Act, which Lord Bingham described as "intensely practical and admirably user-friendly" when it was first published. The fifth edition has been updated by considering in excess of 300 new cases decided since publication of the 4th edition. In addition there have been some significant changes to the Model Law since publication of the previous edition, (which take it into areas where UK arbitration does not go), and these.
Small Claims Arbitrationin the County CourtAppointment of Judgesas Arbitrators; Statutory Arbitrations; Part IIIRecognition and Enforcementof Certain Foreign AwardsEnforcement of GenevaConvention Awards; Recognition and Enforcement ofNew York Convention Awards; Part IVGeneral Provisions; Schedules; Part 3 Appendices; The Arbitration Act 1996 (Commencement No. 1) Order 1996; The Unfair Terms in Consumer Contracts Regulations 1999 (SI 1999 No. 2083); The Arbitration Act 1950, Part II; Table of Cases; Index to Commentary.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Arbitration and award -- England; Arbitrage (Droit) -- Angleterre; LAW -- Civil Procedure; LAW -- Legal Services; POLITICAL SCIENCE -- Government -- Judicial Branch; Arbitration and award; England